Determinants of adoption of butternut squash (Cucurbita moschata) farming among small-holders in Suba district, Kenya - Isaboke, Hezron N.; Mshenga, Patience; Mutai, B.K.; Saidi, M. (My University, 2012)
Butternut squash (Cucurbita moschata) is an emerging economic crop in Kenya with ready market and high nutritional value. Despite this, its adoption as a major cash crop in Suba District has remained low. The aim of the study was to investigate the determinants of adoption and extent of adoption of butternut squash. The study area was chosen due to persistence of poverty despite the fact that the area has conditions that are favourable for the production of high value crops like butternut squash. Cross-sectional data were collected from a sample of 120 farmers selected through multi-stage sampling. The data were subjected to the Heckman two-step regression analysis to obtain the determinants of adoption and the extent of adoption. Data obtained revealed that the adopters of butternut squash were mostly the male married farmers. Results further showed that household size, land tenure, access to credit, membership to a group, market information and access to extension services significantly and positively affected the likelihood of adopting butternut squash; while age, participation in off-farm activities and distance to the market were significant with negative effect. Education, access to market information, man hours and years of experience were significantly related to adoption of the crop with positive effects, while land size was statistically significant with a negative effect. This study therefore, recommends that government and other stakeholders should formulate and implement policies related to promotion of adoption and production of butternut squash.
Keywords: Adoption; butternut squash; Heckman two-step model; Kenya